Subdistrict Administrative Organization Cultural Management Powers and Duties - Klomklung, Pakuna (CRRU Law, Political Science and Social Science Journal, 2023)
Cultural management was the responsibility of subdistrict Administrative Organizations (SAOs) according to Determining Plans and Process of Decentralization to Local Government Organization Act, B.E. 2542 (1999) and the Sub-district Council and Sub-district Administrative Authority Act, B.E. 2537 (1994). In addition, an action plan was issued, defining the decentralization process to local government organizations to formulate guidelines for providing each type of public service. However, the legislation regarding SAOs did not clearly or comprehensively define their scope of cultural management-related Authority. There was also a overlapping cultural management problem between the SAO, central government and local government and subdistrict cultural council. In addition, SAO lacks capacity to carry out cultural management, there were problems of expertise, budget, and cooperation between SAOs. Therefore, SAO laws and guidelines should be revised.